2014
DOI: 10.4049/jimmunol.1203524
|View full text |Cite
|
Sign up to set email alerts
|

Human Procaspase-1 Variants with Decreased Enzymatic Activity Are Associated with Febrile Episodes and May Contribute to Inflammation via RIP2 and NF-κB Signaling

Abstract: The proinflammatory enzyme caspase-1 plays an important role in the innate immune system and is involved in a variety of inflammatory conditions. Rare naturally occurring human variants of the caspase-1 gene (CASP1) lead to different protein expression and structure and to decreased or absent enzymatic activity. Paradoxically, a significant number of patients with such variants suffer from febrile episodes despite decreased IL-1β production and secretion. In this study, we investigate how variant (pro)caspase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 28 publications
(32 reference statements)
3
35
0
4
Order By: Relevance
“…Enhanced interaction between caspase-1 and ASC in cells carrying Ch-C284A compared with Ch-WT cells, which we determined through co-immunoprecipitation and FLIM-FRET, supports this hypothesis. Previously, a similar mechanism was suggested for the interaction between procaspase-1 and RIP2 (14).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Enhanced interaction between caspase-1 and ASC in cells carrying Ch-C284A compared with Ch-WT cells, which we determined through co-immunoprecipitation and FLIM-FRET, supports this hypothesis. Previously, a similar mechanism was suggested for the interaction between procaspase-1 and RIP2 (14).…”
Section: Discussionsupporting
confidence: 54%
“…Numerous pro-inflammatory proteins, including PYPAF1, PYPAF5, PYPAF7, and pyrin, may interact with ASC or procaspase-1 either through their CARD or pyrin domain (48 -51). In support of this hypothesis, procaspase-1 variants with disturbed enzymatic activity have been shown to enhance RIP2-mediated NF-B responses in HEK293T cells (14). Caspase-1/RIP2 interactions, however, have been suggested to occur prior to inflammasome assembly (51).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Intriguingly, some patients with variants of the caspase 1 gene, which encode for forms of procaspase 1 with greatly reduced or absent enzymatic activity, frequently exhibit fever even though levels of IL-1b are low. 183 The latter study demonstrated that the CARD domain of these procaspase 1 variants binds to the CARD of RIP2 to trigger activation of NFkB and presumably downstream inflammatory responses that underpin the regular febrile episodes.…”
Section: Rip2 and Nod Signallingmentioning
confidence: 93%